THE ROLE OF RELIGIOUS INFLUENCERS IN THE DA'WAH DIGITAL SYSTEM A STUDY OF OPPORTUNITIES AND CHALLENGES IN THE COMMUNITY - Ahmad Soleh; Tria Patrianti (Yasi Learning Education Research, 2025)
This study aims to examine the role of religious inOluencers in digital da'wah in Indonesia, a country with a majority Muslim population. Despite the signiOicant potential to disseminate Islamic teachings through modern technology, communication barriers hinder the understanding of these teachings. Da'wah communication is considered crucial in Islam to attain the best rewards. The research methodology is qualitative with a descriptive approach. The results indicate that religious inOluencers bear a signiOicant responsibility in accurately and effectively conveying religious teachings through various communication channels. While easy access to online information presents opportunities, challenges such as misinformation dissemination and societal resistance need to be addressed. To overcome these obstacles, inOluencers must become intelligent, adaptive communicators who build trust with their audiences. By bridging tradition with technology, digital da'wah can serve as an effective means to responsibly disseminate religious values in the continuously evolving digital era.